THE EFFECT OF ADDING AN EXTERNAL MUFFLER WITH A REHEATER TO CAR MUFFLERS ON EXHAUST EMISSIONS - Ahmad Masrueb (Automotive Science and Education Journal, 2024)
Using motorized vehicles can harm the environment, especially the exhaust gas from combustion residue. This study aimed to determine the effect of adding a reheater attached to an external exhaust muffler on vehicle exhaust emissions. The method used in this research is experimental. The independent variable used is the addition of an external exhaust with a reheater temperatur of 140 °C, 160 °C, and 180 °C. The dependent variables in this study are carbon monoxide (CO) and hydrocarbon (HC) exhaust emissions. The control variables in this study include engine oil temperatur (80ºC), no load, standard exhaust used, exhaust gas analyzer brand used (KRISBOW 4-Gas Gasoline), and a U-type finned heater. The results of this study indicate a reduction in CO and HC emissions. The test results of the standard exhaust and external exhaust with the addition of a temperatur variation reheater of 140 °C, 160 ℃, and 180 ℃ the value of CO exhaust gas emission levels decreased by 39%. HC exhaust gas decreased by 27%, with the lowest average CO exhaust gas value of 2.52%, and the lowest HC flue gas was an average of 327 ppm, obtained for each reheater temperatur variation of 180°C. The higher temperatur of the Reheater used causes a decrease in the value of CO and HC exhaust emission levels.